The influence of a grandfather’s disease process and death on the formation of personal identity in a granddaughter - Sellers, Debra M.; Milton, Maggie (My University, 2007)
This case study investigated the influence of a grandfather with Parkinson's disease and his death on the development of personal identity in his granddaughter. The case was complicated by the granddaughter's diagnosis at age 20 with a potentially terminal illness 3 months after his death. The granddaughter experienced symptoms similar to those of her grandfather. Analysis of a retrospective interview with the granddaughter revealed four themes: shared interests, coping skills and adaptation, enlightenment, and influence. These themes were examined within the context of Erik H. Erikson's (1950) theory of identity development as a conceptual framework for understanding the influence of the grandfather-granddaughter relationship.
Keywords: Grandfathers; Death; Personal identity; Case study; Granddaughters